Pembinaan Terhadap Narapidana Hukuman Mati dan Seumur Hidup pada Lembaga Pemasyarakatan Kelas IIA Banda Aceh - Saputra, Suryadi Jaya; Rahmah, Siti; Fazzan, Fazzan (Islamic Family Law Department, Sharia Faculty, Stai Syekh Abdur Rauf, Aceh Singkil, 2025)
The correctional system aims to rehabilitate inmates, including those with severe sentences such as the death penalty and life imprisonment, so they can become better individuals. This study examines the implementation of coaching programs for death row and life-term inmates at the Class IIA Correctional Institution in Banda Aceh. The research objective is to identify and describe the coaching patterns, the obstacles encountered, and the efforts made to overcome these challenges. This study employs a juridical-empirical research method with a sociological legal approach. Data were collected through primary methods, including interviews and observations, and secondary data from literature and regulations. The findings reveal that the coaching programs cover personality development (mental and spiritual) and self-reliance (skills training). Key obstacles include internal factors from the inmates, such as a lack of awareness and resistance; systemic issues like prison overcapacity and limited resources; and external challenges, including negative societal stigma. The institution addresses these obstacles through specialized psychological approaches, improving facilities, enhancing staff human resources, and collaborating with external parties. [Sistem pemasyarakatan bertujuan untuk membina narapidana, termasuk mereka yang divonis berat seperti hukuman mati dan seumur hidup, agar menjadi pribadi yang lebih baik. Penelitian ini mengkaji pelaksanaan program pembinaan bagi narapidana hukuman mati dan seumur hidup di Lembaga Pemasyarakatan Kelas IIA Banda Aceh. Tujuan penelitian adalah untuk mengetahui dan menjelaskan pola pembinaan, hambatan yang dihadapi, serta upaya yang dilakukan untuk mengatasi hambatan tersebut. Penelitian ini menggunakan metode yuridis empiris dengan pendekatan hukum sosiologis. Pengumpulan data dilakukan melalui data primer berupa wawancara dan observasi, serta data sekunder dari literatur dan peraturan. Hasil penelitian menunjukkan bahwa program pembinaan mencakup pembinaan kepribadian (mental dan spiritual) serta kemandirian (keterampilan). Hambatan utama berasal dari faktor internal narapidana seperti kurangnya kesadaran dan penolakan, faktor sistemik seperti overcapacity dan keterbatasan sumber daya, serta faktor eksternal berupa stigma negatif masyarakat. Upaya mengatasi hambatan ini dilakukan melalui pendekatan psikologis khusus, perbaikan sarana, peningkatan kualitas SDM petugas, dan kerjasama dengan pihak eksternal.]